Envisioning multilingualism in source-based writing in L1, L2, and L3: The relation between source use and text quality - Chau, Luan Tuyen; Leijten, Marielle; Bernolet, Sarah; Vangehuchten, Lieve (Frontiers in Psychology, 2022)
In this article, we report on a study that investigates how master's students consult external sources for reading-to-write integrated tasks in their L1 (Dutch), L2 (English), and L3 (French). 280 master's students in professional communication wrote synthesis texts based on three external sources, including a report, a web text, and a newspaper article in their L1 (Dutch), and in L2 (English), or L3(French) at two moments of measurement, which were separated by an interval of 6 months. Their cognitive writing processes were registered using the Inputlog keylogging program. Inputlog enabled us to measure how much time the writers spent composing their main texts and consulting the sources (when they did so, which sources they read most frequently, and how frequently they switched between the various sources). Final text quality was assessed holistically using pairwise comparisons (D-pac, now Comproved). Confirmatory factor analysis indicated three components that could describe source use processes in L1, L2, and L3 writing: (a) initial reading time, (b) source interaction, and (c) variance of source use throughout the writing process. Within-subject comparisons revealed that the students’ text quality remained stable in L1, L2, and L3 over an academic year. Structural equation modeling indicated that the source use approach, particularly source interaction, is related to text quality, but only in L1 and L3. We provide further explanations for this variation based on language proficiency, temporal distribution of writing process, and individual differences.